Cerebrospinal fluid analysis - POLIZOPOULOU (Ζ.Σ. ΠΟΛΥΖΟΠΟΥΛΟΥ), Z. S. (Journal of the Hellenic Veterinary Medical Society, 2017)
The significance of cerebrospinal fluid (CSF) analysis has been compared to that of complete blood counts for systemic diseases. CSF changes generally follow specific patterns depending on the etiopathogenesis (inflammatory, metabolic, neoplastic) of neurological diseases, thus indicating which further diagnostic modalities should be applied. CSF collection requires operator skills and knowledge of sampling indications and contraindications. Analysis includes physical examination (colour, clarity, viscosity), cytological and biochemical analysis, microbiological and immunologic testing. Despite its limitations, CSF analysis is a useful diagnostic tool, in particular when results are interpreted in combination with historical information, clinical examination and the findings of clinicopathological and diagnostic imaging testing.